'Have you wondered why sportspeople die?' The medical weblog as a popularisation tool. (October 2018) - Sokół, Małgorzata
Highlights: Popularisation and self-expression intertwine in medical blogs. Popularisation strategies in use reflect the heterogeneity of the blogs' audiences. Rhetorical strategies of popularisation that engage the audience prevail. The audience is empowered to co-construct knowledge. Abstract: The paper considers the role of medical blogging practices in Poland, and more specifically, aims to explore the use of popularisation strategies in medical weblogs. Following recent approaches to the study of online communication in healthcare contexts that emphasise the importance of the interpersonal aspect, the study of blogging practices among Polish medical practitioners uses discourse analysis to examine healthcare practitioners' professional identity via their engagement in popularisation. The qualitative analysis of the blog posts explores, and illustrates in detail, the popularisation strategies employed by healthcare practitioners. Healthcare practitioners effectively exploit the affordances of the blog to share knowledge and inform, e.g. through detailed explanations of terms, examples from everyday life and relevant contextual information via links, but also to educate and entertain, e.g. through the use of humour and irony, or narratives of professional and personal experience. The analysis also reveals that popularisation intertwines with self-expression in the medical weblog. The bloggers engage in self-disclosure and evaluative expression, use conversational, colloquial language, but at the same time they show that they are close to patients' everyday experience.